Positive correlation between postoperative tumor recur-rence and changes in circulating tumor cell counts in pul-monary venous blood (pvCTC) during surgical manipulation in non-small cell lung cancer - Hashimoto, Masaki; Tanaka, Fumihiro; Yoneda, Kazue; Takuwa, Teruhisa; Matsumoto, Seiji; Okumura, Yoshitomo; Kondo, Nobuyuki; Tsujimura, Tohru; Nakano, Takashi; Hasegawa, Seiki (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Background: In non-small cell lung cancer (NSCLC), circulating tumor cells (CTC) are shed and circulate to the peripheral blood through the pulmonary vein. Previously, CTC count in pulmonary venous blood (pvCTC) was shown to significantly increase after surgical manipulation. Therefore, we assessed the correlation between the changes in the pvCTC count (ΔpvCTC) and clinical outcomes. Methods: Consecutive patients with peripheral-type, NSCLC, who underwent lobectomy or bi-lobectomy through open thoracotomy, were enrolled prospectively. Before and after lobectomy, 2.5 mL of blood was drawn from the associated lobar pulmonary vein (PV), and was served for the quantitative evaluation of CTC using the CellSearch® system. The cut-off point of ΔpvCTC was determined according to clinical outcomes and ΔpvCTC using receiver operation characteristic (ROC) curve. Then the correlation between ΔpvCTC and clinical outcomes was evaluated by Kaplan-Meier analyses and log-rank test. In addition, the correlation between ΔpvCTC and perioperative variables was assessed. Results: A total of 30 patients were enrolled, tumor recurrence occurred in 11 patients over a median follow-up of 64.4 months. Of these, 7 patients had distant metastasis and 4 had local recurrence. The median ΔpvCTC was 49 cells/2.5 mL, and pvCTC-count was increased during surgical manipulation in 24 patients (80%). We divided patients into two groups based on ΔpvCTC with the cut-off value as 119 cells/2.5 mL according to ROC curve. Significant shorter time to distant metastasis (TDM) (P=0.0123) was observed in high ΔpvCTC group (ΔpvCTC ≥119 cells/2.5 mL) than low ΔpvCTC group (ΔpvCTC